Tobacco cessation education through peer-to-peer role-playing: implications for dental students’ future clinical practice. A pilot study - Cloitre Alexandra; Clouet Roselyne; Hascoët Emilie; Prud'homme Tony; Bodard Clémence; Chaux Anne-Gaëlle (Journal of Oral Medicine and Oral Surgery)
Objectives: To assess the impact of a course incorporating role-playing on undergraduate dental students' satisfaction, knowledge, and attitudes toward tobacco cessation counseling. Methods: A pilot study was conducted at a French dental school between September 2022 and March 2023. Overall, 28 fourth- and fifth-year dental students participated in a three-step course on tobacco cessation counseling which included a theoretical component and role-playing sessions. Kirkpatrick’s four-level model was used to assess educational outcomes immediately after the theoretical course (levels 1 and 2) and 6 months later (levels 3 and 4). Results: The level 1 evaluation showed that most students were satisfied with the course (mean score: 4.7/5) and would use their knowledge in their future practice. For level 2, knowledge was significantly increased (+ 36.7%) following the course and was maintained at 6 months (p=0.015). Levels 3 and 4 assessed clinical behaviour and practice regarding tobacco cessation counselling and showed a significant increase in counseling (+28.7%) and in the prescription of tobacco substitutes (+ 48.6%) at 6 months (p=0.042 and 0.041, respectively). Conclusions: The study demonstrated the effectiveness of a role-playing-based course in terms of satisfaction, knowledge, and clinical behavior toward tobacco cessation counselling with sustained knowledge retention over time.